1969
DOI: 10.1172/jci106060
|View full text |Cite
|
Sign up to set email alerts
|

Binding of digitoxin and some related cardenolides to human plasma proteins

Abstract: A B S T R A C T Tritium-labeled digitoxin, digitoxigenin, digoxin, and digoxigenin of established purity and chemcal authenticity were used to study the binding of these compounds to human plasma proteins. 97% of digitoxin in plasma was nondialyzable. Continuous flow paper electrophoresis of plasma containing digitoxin and dialysis experiments in which human serum albumin competed for the glycoside with plasma or plasma protein fractions demonstrated that digitoxin was almost exclusively bound by albumin. Equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

1970
1970
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(44 citation statements)
references
References 38 publications
5
38
1
Order By: Relevance
“…We have previously reported a mean value of 97.3% (SD 0.4) in an adult control group (41), a value in good accordance with the 97 % reported by Lukas and deMartino (24).…”
Section: Laboratory Methodssupporting
confidence: 89%
“…We have previously reported a mean value of 97.3% (SD 0.4) in an adult control group (41), a value in good accordance with the 97 % reported by Lukas and deMartino (24).…”
Section: Laboratory Methodssupporting
confidence: 89%
“…The rapid second-order association kinetics ensure that the free fraction of serum digitoxin concentration will fall to less than 1 nM within a few seconds of the infusion of antibody in the amount used in the experiments reported here, assuming rapid mixing in the intravascular compartment. This rapid binding of digitoxin by antibody occurs in spite of extensive serum albumin binding of digitoxin (14) because of the very rapid dissociation rate of the digitoxin-albumin complex. It should be noted that the degree of digitoxin crossreactivity noted in the present studies cannot be expected for every digoxin-binding antibody population (23).…”
Section: Resultsmentioning
confidence: 99%
“…Lukas and DeMartino demonstrated that 97% of digitoxin at usual therapeutic concentrations is bound to serum albumin (14). An effective approach to the specific treatment of advanced digitoxin intoxication, then, ideally should enhance excretion ofthe drug as well as neutralize its effects before excretion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of both "digoxin-like immunoreactive factors" and digoxin to protein is markedly temperature-dependent (34,39). At 37 °C, 20-25% of digoxin is bound to plasma proteins, but only about 5% is bound at 4 °C.…”
Section: Discussionmentioning
confidence: 99%